Bacteremia during tonsillectomy - Kaygusuz, I; Gök, Ü; Yalçin, S; Keles, E; Kizirgil, A; Demirbag, E (Elsevier Sci Ireland Ltd, 2001)
Objective: To investigate bacteremia in patients who underwent tonsillectomy with a dissection method due to chronic tonsillitis. which may lead to dramatic results in patients that have a cardiovascular infection risk. In this study. it was explored whether the tonsil surface and the tonsil tissue interior microorganisms are different or not, and whether these microorganisms carry bacteremia development risk. Methods: Forty patients were enrolled in the study in ENT Clinic, Firat University. A bacteriological research was performed on patients with no treatment with antibiotics for a month before the operation. Tonsil surface and deep tissue cultures were performed, and venous blood samples were taken for cultures before and after the operation. Results: Surface acid deep tissue cultures of tonsils of the cases represented a different result in 27.5% of the patients. No reproduction was observed regarding the blood cultures taken before tonsillectomy. Bacteremia was found in blood samples of ten patients (25%) taken immediately after tonsillectomy. Conclusion: Hence, it has been concluded that different microorganisms may be present among the tonsil surface and tonsil deep tissue cultures and that bacteremia may develop after tonsillectomy. Therefore, to prevent the possible dramatic outcomes after tonsillectomy the required measures during the preoperative period should be taken into consideration, especially in patients that have chronic tonsillitis with cardiovascular disease. (C) 2001 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: tonsillectomy; bacteremia; prophylaxis